2020
DOI: 10.5271/sjweh.3927
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of changes in interactional justice and subsequent short-term sickness absence among municipal employees

Abstract: A longitudinal study of changes in interactional justice and subsequent short-term sickness absence among municipal employees by Koskenvuori M, Pietiläinen O, Elovainio M, Rahkonen O, Salonsalmi A Negative change in interactional justice was associated with highest risk of short-term sickness absence. The association was found in between-and within-individual modelling. The association was higher in between-individual modelling, suggesting that unobserved, stable differences between the individuals play role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…OJ has stronger effects when employees perceive high job demands, have low job control or low social support [60], when they are in situations of job insecurity [49,78], and in times of uncertainty [90]. When it comes to justice variability levels, as Koskenvuori et al [25] have shown, an unfavorable change in OJ could be more detrimental than stable low levels of justice. In an experimental study conducted by Matta et al [26], similar conclusions were found, as being treated unfairly on a consistent basis was less stressful (in terms of heart rate and heart rate variability) than being fairly, but variably so.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…OJ has stronger effects when employees perceive high job demands, have low job control or low social support [60], when they are in situations of job insecurity [49,78], and in times of uncertainty [90]. When it comes to justice variability levels, as Koskenvuori et al [25] have shown, an unfavorable change in OJ could be more detrimental than stable low levels of justice. In an experimental study conducted by Matta et al [26], similar conclusions were found, as being treated unfairly on a consistent basis was less stressful (in terms of heart rate and heart rate variability) than being fairly, but variably so.…”
Section: Discussionmentioning
confidence: 99%
“…e uncertainty model could also help to explain the impact of changes in OJ [25,26], because justice variability could be considered a source of uncertainty itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations